TINJAUAN YURIDIS TERHADAP PERTIMBANGAN HAKIMYANG TIDAK LENGKAP (ONVOLDOENDE GEMOTIVEERD) DALAM PENJATUHAN PIDANA DI BAWAH ANCAMAN PIDANA MINIMAL DALAM TINDAK PIDANA NARKOTIKA (STUDI KASUS PUTUSAN NOMOR 46/PID.SUS/2023/PN MRN) - Mia Ramadani (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
The contents that must be contained in a court decision are regulated in the provisions of Article 50 paragraph (1) of Law Number 48 of 2009 concerning Judicial Power and Article 197 of the Criminal Procedure Code. A decision that does not meet these provisions is an incomplete decision or insufficient consideration (onvoldoende gemotiveerd). Meuredu District Court Decision Number 46/Pid.Sus/2023/PN Mrn is a decision in a narcotics crime case where the Defendant is subject to Article 112 Paragraph (1) of Law Number 35 of 2009 concerning Narcotics, the minimum penalty for which is 4 (four) years in prison. However, the Panel of Judges imposed a prison sentence under the minimum penalty, namely 2 (two) years in prison without stating and explaining the legal basis used as a reference in imposing a sentence under the minimum penalty. This research aims to find out and analyze whether the judge's considerations in Decision Number 46/Pid.Sus/2023/PN Mrn do not contain complete legal considerations and what are the legal consequences of the judge's decision whose considerations are incomplete. This research is a normative legal research using the statutory approach method and case approach. Data sources were obtained from literature review and secondary data, namely primary, secondary, and tertiary legal materials which were analyzed qualitatively. The results showed that the judge's consideration in Decision Number 46/Pid.Sus/2023/PN Mrn, was an insufficient consideration because the judge did not include SEMA Number 3 of 2015 which is a legal basis that legitimizes judges to be able to deviate from the minimum criminal provisions in narcotics crimes. So that this decision does not create legal certainty and legal remedies need to be taken to be able to correct mistakes in the application of law by judges. These legal remedies are ordinary legal remedies or extraordinary legal remedies.